Uncovering the Underlying Mechanisms of Ketamine as a Novel Antidepressant - Xu, Songbai; Yao, Xiaoxiao; Li, Bingjin; Cui, Ranji; Zhu, Cuilin; Wang, Yao; Yang, Wei (Frontiers in Pharmacology, 2022)
Major depressive disorder (MDD) is a devastating psychiatric disorder which exacts enormous personal and social-economic burdens. Ketamine, an N-methyl-D-aspartate receptor (NMDAR) antagonist, has been discovered to exert rapid and sustained antidepressant-like actions on MDD patients and animal models. However, the dissociation and psychotomimetic propensities of ketamine have limited its use for psychiatric indications. Here, we review recently proposed mechanistic hypotheses regarding how ketamine exerts antidepressant-like actions. Ketamine may potentiate α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor (AMPAR)-mediated transmission in pyramidal neurons by disinhibition and/or blockade of spontaneous NMDAR-mediated neurotransmission. Ketamine may also activate neuroplasticity- and synaptogenesis-relevant signaling pathways, which may converge on key components like brain-derived neurotrophic factor (BDNF) / tropomyosin receptor kinase B (TrkB) and mechanistic target of rapamycin (mTOR). These processes may subsequently rebalance the excitatory/inhibitory transmission and restore neural network integrity that is compromised in depression. Understanding the mechanisms underpinning ketamine’s antidepressant-like actions at cellular and neural circuit level will drive the development of safe and effective pharmacological interventions for the treatment of MDD.